Association between academic motivation and burnout in dental students at the Tabriz University of Medical Sciences: A longitudinal study - Fatemeh Pournaghi Azar; Parnian Alizadeh Oskoee; Saeedeh Ghaffarifar; Nafiseh Vahed; Saba Shamekhi (Tabriz University of Medical Sciences, 2020)
Background: Health professions students often experience stress and potential burnout while completing their entry-to-practice education; therefore, detecting and monitoring burn out among these students is paramount. This study compared motivation domains and determined the relationship between motivation and academic burnout among students of the Dental Faculty at the Tabriz University of Medical Sciences. Methods: This analytical study was conducted longitudinally with dental students at the Tabriz University of Medical Sciences beginning from 2012, the first semester of the participating first-year students and then in the final semester when the same students graduated in 2017.All students (N = 110) were invited to participate. Academic motivation was assessed using the Valler and Academic Motivation Scale. Comparison between first and last semester motivation scores and the relationship between academic motivation level and burnout subscales was determined using independent t-tests and Pearson's correlation coefficient tests. SPSS was used for the statistical analysis; P < 0.05 was considered statistically significant. Results: Gender had a statistically significant effect on extrinsic motivation and a motivation: in both the first and last semesters, male students were less extrinsically motivated (P < 0.05).Pearson's correlation coefficient test found a significant inverse correlation between intrinsic and extrinsic motivation of students in their final semester and the academic efficacy (EF)subscale (r = -0.25, P = 0.015; r = -0.21, P = 0.03, respectively). Conclusion: Results showed that although there was a decrease in motivation level, students had high motivation and low burnout level in their final semester compared to their first semester. Extrinsic motivation was higher than intrinsic at both stages